Anthropometric Indexes for Predicting High Blood Pressure in Vietnamese Adults: A Cross-Sectional Study - Nguyen Minh Q; Nguyen Vo MH (Dove Medical Press, 2020)
Quan Nguyen Minh,1 Minh Hoang Nguyen Vo2 1Thu Duc District Hospital, Ho Chi Minh City, Vietnam; 2Office of Science Management and International Affairs, Thu Duc District Hospital, Ho Chi Minh City, VietnamCorrespondence: Minh Hoang Nguyen VoThu Duc District Hospital, Ho Chi Minh City, VietnamTel +84389135014Email minhhoangytcc87@gmail.comBackground: The rate of hypertension and obesity is increasing in Vietnamese society. This study aimed to focus on assessing the relationship between anthropometric indexes (body mass index (BMI), waist-to-height ratio (WHtR), waist-to-hip ratio (WHR)) and high blood pressure to determine which is the best predictor for high blood pressure among adults over 18 years in Vietnam.Methods: A cross-sectional study of 1636 people was conducted. People who were over 18 years old, healthy or had hyperlipidemia and on the treatment were recruited. Patients with cancer, heart disease, diabetes, kidney disease, and hypertension were excluded. Information on demographics, smoking and drinking habits, weight, height, waist circumference, and blood pressure was collected. Areas under receiver operating characteristic curves (AUCs) were examined to determine the predictability of anthropometric indicators for high blood pressure in men and women. Logistic regression analysis, stratified by gender, was performed to examine the association between anthropometric indexes and high blood pressure.Results: In this study, the percentage of people with high blood pressure was 10.51%. The AUC for the WHtR was significantly greater than for the BMI for both genders. Logistic regression demonstrated that only WHtR had a significant positive association with high blood pressure among women. The optimal WHtR cut-off value for predicting high blood pressure in men and women were 0.47 and 0.50, respectively.Conclusion: Among the indicators analyzed in this study, WHtR was the best for the predicting of the presence of high blood pressure, in both men and women. However, WHtR could only explain the changes of high blood pressure in women.Keywords: high blood pressure, waist–hip ratio, waist–height ratio, body mass index, high blood pressure prediction